1 Answer | Add Yours
Let's rearrange the equations of the lines as below.
`x+by+c = 0`
`by = -x-c`
`y = -1/bx-c/b`
This has a x intercept of 4. That means when y = 0, x=4.
`4+0+c = 0`
`c = -4`
`x+2by+c = 0`
`2by = -x -c`
`y = -1/(2b)x-c/(2b)`
The given equations are parallel. Therefore,
`-1/b = -1/(2b)`
`2b = b`
This can only happen only if `b = 0` .
Therefore, the both equations reduces
`x+c = 0`
`x-4 = 0`
Therefore the x-intercept of second equation is also 4.
We’ve answered 333,453 questions. We can answer yours, too.Ask a question